Endothelial Insulin Resistance of Freshly Isolated Arterial Endothelial Cells From Radial Sheaths in Patients With Suspected Coronary Artery Disease. Issue 6 (19th March 2019) - Masaki, Nobuyuki; Ido, Yasuo; Yamada, Toshiyuki; Yamashita, Youhei; Toya, Takumi; Takase, Bonpei; Hamburg, Naomi M.; Adachi, Takeshi
Abstract : Background: Endothelial insulin resistance is insulin‐insensitivity in the vascular endothelium and can be observed in experimental models. This study aimed to investigate endothelial insulin resistance in patients with suspected coronary artery disease. To this end, a novel method of obtaining freshly isolated arterial endothelial cells from a radial catheter sheath was developed. Methods and Results: Freshly isolated arterial endothelial cells were retrieved from catheter sheaths placed in radial arteries for coronary angiography (n=69, patient age 64±12 years). The endothelial cells were divided into groups for incubation with or without insulin, vascular endothelial growth factor, or acetylcholine. The intensity of phosphorylated endothelial nitric oxide synthase at Ser1177 (p‐eNOS) was quantified by immunofluorescence microscopy. The percentage increase of insulin‐induced phosphorylated endothelial nitric oxide synthase correlated negatively with derivatives of reactive oxygen metabolites, an oxidative stress test ( r =−0.348, n=53, P =0.011), E/E′, an index of left ventricular diastolic dysfunction in Doppler echocardiography (ρ=−0.374, n=49, P =0.008), and log‐transformed brain natriuretic peptide ( r =−0.266, n=62, P =0.037). Furthermore, percentage increase of insulin‐induced p‐eNOS was an independent factor for the cardio‐ankle vascular index (standardized coefficient β=−0.293, n=42, P =0.021) in the multivariate regression analysis of adaptive least absolute shrinkage and selection operator. Conclusions: Our results suggested that endothelial insulin resistance is associated with oxidative stress, left ventricular diastolic dysfunction, heart failure, and arterial stiffness.